Gambaran Pengetahuan Mahasiswa Tingkat Satu Diploma Tiga Refraksi Optisi Tentang Kelainan Refraksi - Jaja Muhammad Jabbar; Rafhi Ghani Mahenra (stikes dharma husada bandung, 2021)
Eyes health is the most important thing in getting visual information to do daily activities. But visual disturbance or refraction disorders, experienced by many people and it cannot be ignored because they can disturb activities. Each people need to know about those kinds of refraction disorders. That way, it is expected that people can anticipate the symptoms of this refraction disorder. Knowledge of refraction disorder such as myopia, hypermetropy, and astigmatism is important for all people, especially for people who are steeped in the field of optical refraction. The purpose of this research is to know about refraction disorders knowledge of the first grade optition refraction students. The method that used in this research is descriptive quantitative, which the data from research sample is analyzed corresponding to statistic method that being used. While the instrument is questionnaire in the form of closed questions. The population is 54 regular university students majoring in optical refraction. Result of the research shows that 38% students in a good category, 44 % students are enough and the rest 18 % are in the poor category. Based on the result of the research, a solution is needed to improve students knowledge about optical refraction disorder.